Catalytic hydrothermal liquefaction of Spirulina over bifunctional catalyst to produce high-quality biofuel. (15th December 2020) - Wang, Huansheng; Tian, Wenying; Zeng, Fangang; Du, Hongbiao; Zhang, Jinglai; Li, Xing
Highlights: Five different bifunctional catalysts are characterized and applied for the HTL of Spirulina . The XRD, NH3 -TPD and BET analysis results show NiO/SAPO-34 and NiO/USY catalysts have the relatively superior properties. The bio-oil contains the highest HHV (34.58 MJ/kg) and the most hydrocarbons (20.58%) with NiO/USY catalyst. NiO/USY can promote the macromolecular-cracking reaction and the formation of light oil components in the HTL. Abstract: In this study, five different bifunctional catalysts (NiO/SAPO-34, NiO/ZSM-5, NiO/USY, NiO/γ-Al2 O3 and NiO/SiO2 ) are characterized and applied for the hydrothermal liquefaction (HTL) of Spirulina to produce biofuel. The X-ray diffraction (XRD), ammonia desorption measurement (NH3 -TPD) and Brunauer-Emmet-Teller (BET) analysis results show that NiO/SAPO-34 and NiO/USY catalysts have the better physical properties compared to the other three catalysts, resulting in the higher bio-oil yields of 59.85 wt% and 59.12 wt%, respectively. Then the bio-oil samples are characterized by elemental analysis, Gas Chromatography-Mass Spectrometry (GC–MS) and Thermo-gravimetric analysis (TGA). Results indicate that the bio-oil obtained over NiO/USY catalyst has the highest higher heating value (HHV) due to the higher C and H content as well as the lower O and N content. What's more, it contains the most hydrocarbons (20.58%) and light oil components (72.91%) with NiO/USY catalyst. Consequently, NiO/USY is considered to be the best bifunctional catalyst for the HTL of Spirulina .